2016
DOI: 10.2147/ijwh.s99943
|View full text |Cite
|
Sign up to set email alerts
|

One-year assessment of physical activity level in adult Qatari females: a pedometer-based longitudinal study

Abstract: BackgroundPhysical inactivity is a growing health concern and has been identified as the fourth leading risk factor for global mortality. The Arab region includes countries with some of the world’s highest physical inactivity levels, such as Qatar, more specifically the Qatari female population.ObjectiveThe objective of this study is to assess the physical activity levels of Qatari national female adults during a 1-year pedometer-based program.Materials and methodsA total of 549 Qatari national females aged be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 30 publications
3
56
0
Order By: Relevance
“…Residing close to parks was related to higher levels of PA . Furthermore, being married, working in the private sector, working two shifts, or having only 1 day off during the week were associated with low PA . Participants with more family members were physically less active .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Residing close to parks was related to higher levels of PA . Furthermore, being married, working in the private sector, working two shifts, or having only 1 day off during the week were associated with low PA . Participants with more family members were physically less active .…”
Section: Resultsmentioning
confidence: 95%
“…However, one study showed that age was not a significant correlate of physical inactivity . Another study showed that women aged 45 to 64 years were more active than younger women . While some studies indicated that higher educational and occupational status were associated with lower PA in the Gulf States, other studies showed the opposite .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations